Assessment of absorbing aerosols on austral spring snow albedo reduction by several basins in the Central Andes of Chile from daily satellite observations (2000–2016) and a case study with the WRF‑Chem model - Bolaño Ortiz, Tomás Rafael (2019)
Fil: Bolaño Ortiz, Tomás R. Universidad Tecnológica Nacional. Facultad Regional Mendoza. Grupo de Estudios Atmosféricos y Ambientales; Argentina